Case report of isolated impaling lung injury with successful outcome - Goel, Tushar; Bhate, Sameer (International Surgery Journal, 2017)
Impalement thoracic injuries are rare of great importance due to severity and high chances of mortality. It is essential to prevent possible vascular injury by the object avoiding major haemorrhage. This study’s primary objective is to discuss 22-year-old male patient admitted in emergency with impaling thoracic trauma by metallic sharp object post battery blast at home. X-ray reveals linear foreign body: penetrating thorax and lung. CT Chest was done and assessment was made for further management with cardiothoracic department. Patient details were collected by patient’s IPD file. Complete detailed history, patient vitals, hemogram, ABO, ABG, CXR along with USG chest and abdomen and CECT chest was done. Post op daily chest X-ray and hemogram along with chest physiotherapy and spirometry was done. Treatment diagnosis was impaled linear foreign body penetrating thorax and lung, patient was shifted to OT, under GA sternotomy was performed. Foreign object passing just lateral to subclavian penetrating upper pole of lung was identified and under specific vision pulled out carefully through entry wound keeping in mind vascular trauma. Necrosed lung part was stapled and wedge resected, on POD 8 patient was discharged with satisfactory condition. Impalement thoracic traumas are rare and have high mortality. Selection of line of treatment is necessary. Indication of surgery under high risk is performed for further trauma. In our case sternotomy was planned and under specific vision impaled object which was passing just by subclavian penetrating through lung was removed safely and patient went home in good condition.